Getting it RITE: Impact of a Dedicated Hospital Medicine Curriculum for Residents. Issue 1 (January 2018) - Lin, Doris; Shah, Chirayu; Campbell, Steffanie; Bates, Jeffrey T.; Lescinskas, Erica
Abstract : Objective: The goal of this study was to improve resident confidence in inpatient care and knowledge in hospital medicine topics with a newly developed rotation and curriculum called the Resident Inpatient Training Experience. Methods: This study was a prospective observational study completed by postgraduate year-2 (PGY-2) internal medicine residents in two affiliated hospitals. Forty-six PGY-2 residents each rotated on the Resident Inpatient Training Experience service for 1 month and completed a pre- and postrotation confidential online survey. Primary outcomes included confidence in managing hospitalized patients, knowledge regarding hospital medicine topics, and interest in pursuing hospital medicine as a career. Results: Thirty-three PGY-2 residents completed both the pre- and postrotation survey (72% response rate). After completing the rotation, the residents' confidence level (measured on a 5-point Likert scale, with 1 = strongly disagree and 5 = strongly agree) rose significantly in managing hospitalized patients, from 3.82 to 4.33 ( P = 0.003) and in leading a ward team, from 3.76 to 4.21 ( P = 0.020). Knowledge level (measured on a 5-point Likert scale with 1 = very poor and 5 = excellent) improved significantly in transitions of care, from 3.45 to 3.79 ( P = 0.023); cost-conscious care, from 3.00 to 3.42 ( P = 0.016); physician billing/coding, from 2.55 to 3.03 ( P = 0.007); hospital metrics, from 2.39 to 2.94 ( P = 0.002); and hospital reimbursement, from 2.48 to 3.09 ( P = 0.001). Interest in pursuing hospital medicine as a career also increased. Conclusions: Resident independence in managing patients and training in hospital medicine topics has not kept up with evolving need. Dedicated hospital medicine rotation and curriculum are effective ways to alleviate the deficiencies in resident education. Abstract : Resident independence in managing patients and education in important hospital medicine topics, including quality improvement, patient safety, billing and coding, and transitions of care, have not kept up with evolving need. Dedicated hospital medicine rotation and curriculum are effective ways to alleviate the training gap in resident education.